Food, Housing, Work, Retirement: Resourcefulness in Everyday Life as an Element of the Functioning of Society and the Economy in the People’s Republic of Poland (Selected Aspects) - Jarosz, Dariusz (Studia Historiae Oeconomicae, 2023)
The article attempts to determine the usefulness of the concept of resourcefulness for research in the field of social history of the People’s Republic of Poland. On the basis of examples concerning problems with provisions, housing, professional work and retirement benefits, an analysis of specific issues was made, where this resourcefulness manifested itself particularly intensively. The research shows that in many cases it was pathological. It meant a strategy of behavior consisting in achieving the assumed goals by individuals or various groups of people using means that are in conflict with the norms, rules, procedures accepted as appropriate in a given political and socio-economic order.